The calculated fraction 47/10 to a mixed number is 4 7/10
From the question, we have the following parameters that can be used in our computation:
Number = 47/10
Convert to a fraction
Number = 47/10
Divide 47 by 10
So, we have
Quotient = 4
Next, we have
Remainder = 47 - 4 * 10
Evaluate the products
Remainder = 7
So, we have
Fraction = 4 7/10
Simplify
Fraction = 4 7/10
Hence, the fraction to a mixed number is 4 7/10
Read more about fraction at
#SPJ6
The number would be greater then 36.
An inequality is a relation which makes a non-equal comparison between two numbers or mathematical expressions.
here, we have,
Let x represent the unknown number. The opposite of this number would be represented by -x.
1/3 of this is found by multiplying by 1/3; this gives us
1/3×(-x)
Since it is less than 12, this gives us
1/3×(-x) < 12
To cancel the 1/3, we can multiply both sides by 3:
1/3×(-x)×(3) < 12×(3)
-x < 36
We can cancel the negative by dividing both sides by -1. When we multiply or divide an inequality by a negative number we flip the inequality:
-x/-1 < 36/-1
x > 36
Our number must be greater than 36.
To learn more on inequality click:
#SPJ2
Answer:
The number would be greater then 36.
Step-by-step explanation:
Let x represent the unknown number. The opposite of this number would be represented by -x.
1/3 of this is found by multiplying by 1/3; this gives us
1/3(-x)
Since it is less than 12, this gives us
1/3(-x) < 12
To cancel the 1/3, we can multiply both sides by 3:
1/3(-x)(3) < 12(3)
-x < 36
We can cancel the negative by dividing both sides by -1. When we multiply or divide an inequality by a negative number we flip the inequality:
-x/-1 < 36/-1
x > 36
Our number must be greater than 36.
P(bran muffin) =
Answer:
P = 2/16 This is based on 14/16 chance that the next pastry will be something else.
Step-by-step explanation:
We can also expand and say P= 2/16 = 1/8
Not P= 7/8
3x-2y=19
Y=x-7
Answer:
x = 5 and y = -2
Step-by-step explanation:
Here you have given what y is equal to, this means you can sub this into the first equation:
3x - 2(x - 7) = 19
Expand the brackets:
-2 * x = -2x
-2 * -7 = 14
3x -2x +14 = 19
Move the +14 over to the other side making it a -14:
3x - 2x = 19 - 14
3x - 2x = 5
3x - 2x = x
So x = 5
Now sub this into the first equation:
3(5) - 2y = 19
15 - 2y = 19
Move the -2y over to the other side making it a +2y, and move the +19 over to the other side making it a -19:
15 - 19 = 2y
-4 = 2y
Divide both sides by two:
y = -2
So x = 5 and y = -2